Om att bygga landsbygd : ett ruralt planeringsexperiment i Botkyrka - Henriksson, Elin Sofia (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
I have studied the suburban municipality of Botkyrka, south of Stockholm, from a rural perspective. Through that I`ve compared how countryside comes into being with the planning and building of suburbs. I have looked for a definition of Countryside, and found that it is often explained or defined in negative terms, as what it is not. In that it says nothing about what it really is, or about the qualitiies it has to it. Botkyrka is a suburb, but it does in large parts consist of countryside. Apart from defining countryside and rural I´ve been searching for a definition of suburbia, of it´s structure and the mental picture we have of it as a cultural phenomena. In order to understand the role that suburbs have in planning I describe their history from Italian renaissance villas to sprawl.